Flow Cytometry Evaluation of Blood-Cell-Bound Surface FVIII in Hemophilia A and Thrombosis - Anjud Al-Mohannadi; Reem Mohammed Yahia; Hani Bibawi; Che-Ann Lachica; Watfa Ahmed; Igor Pavlovski; Giusy Gentilcore; Elkhansa Elbukhari Elgaali; Anila Ejaz; Areeg Ahmed; Mohammed Elanbari; Zainab Awada; et al. (Cells)
Hemophilia A (HA) is associated with FVIII coagulation insufficiency or inactivity leading to excessive bleeding. Elevated FVIII, on the contrary, is associated with thrombophilia, thrombosis, myocardial infarctions, and stroke. Active FVIII (aFVIII) uses its C2 domain to bind to blood cells’ membranes, consequently carrying out its coagulative function. We developed a reliable flow cytometry (FC) method for FVIII detection that can be utilized for assessing surface-bound FVIII on leukocytes in different coagulation/clinical states; we analyzed 49 pediatric subjects, encompassing patients with HA, other coagulopathies, venous thrombosis, and normal coagulation. Interestingly, the total leukocyte surface FVIII showed a declining trend across thrombosis, normal, and hypo-coagulation states. As expected, the leukocytes of HA patients displayed significantly lower levels of cellular-surface FVIII in comparison to patients with thrombosis. However, no significant correlation was observed between circulating levels of FVIII in plasma and the levels of FVIII bound to leukocytes, indicating that the differences in FVIII surface binding are not directly proportional to the availability of FVIII in the circulation and suggesting a specific binding mechanism governing the interaction between FVIII and leukocytes. Intriguingly, when analyzing the distinct blood subpopulations, we observed that surface FVIII levels were significantly elevated in classical monocytes of thrombosis patients compared to HA patients, healthy controls, and patients with other coagulopathies. Our study highlights the reliability of our FC platform in assessing FVIII abundance on leukocytes’ membranes across coagulation states. Monocytes, particularly in cases of thrombosis, exhibit active binding of FVIII on their surface, suggesting a potential role in the pathophysiology of thrombosis that requires further investigation.